PERBANDINGAN KARAKTERISTIK DAN PRODUKTIVITAS ULATSUTERA (Bombyx mori L.) DARI TIGA BIBIT HIBRID - Sitti Nuraeni; . Baharuddin (PERENNIAL, 2010)
The purpose of this research to compared the characteristic and productivity of three silkworm seeds. The result of this research can be information for user of the sericulture. Three seeds examination from Perum Perhutani Soppeng ( P1), BS09 ( P2) and C103 ( P3) from Perum Perhutani Candiroto (Central Java).The observation will be done the hatchability of eggs, resistance of larval, and the characteristic of the larval. Result of research shows that stadium of P2 and P3 silkworm is shorter (21 days) than P1 (23 days). Larval characteristic; colored and larval pattern are equal relative except longer caterpillar P1 length from P2 and P3. Cocoon characteristic; colored, wrinkle and its hardness relative is of equal except size measure and form the cocoon, ellipse globular bigger P1 than P2 and P3 are elliptical like peanut. The result of this research was showed that examination three seeds hybrid of productivity observation (hatchability of eggs and resistance of mature larval,) P1 better than P2 and P3. Key words: Characteristic, productivity, hybrid seed, silkworm (Bombyx mori L).